Peningkatan Produktivitas dan Nilai Tambah Usaha Agribisnis Tanaman Rempah di Kampung Wasur, Merauke - Ferdinand Christianto Situmorang; Dandi Saleky (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This community service initiative aims to enhance the productivity and added value of spice crops through an integrated agribusiness approach. The program encompasses training in organic-based spice cultivation and simplified processing techniques to generate value-added products. The training and mentoring activities have proven effective in improving the community's knowledge and skills in processing spices into high-value products, such as instant ginger, kunyit asam (turmeric acid drink), and spice powders. Furthermore, participants have gained a comprehensive understanding of basic packaging and labeling techniques, as well as the strengthening of business management and marketing capacities. It is expected that these activities will not only improve the welfare of local farmers but also establish a spice agribusiness model that can be replicated in other regions of South Papua. Beyond increasing farmers' income, this initiative contributes to local economic resilience and the preservation of traditional knowledge regarding the use of spices as medicinal plants. Through direct community involvement and a participatory approach, this service is anticipated to provide a long-lasting impact on building a sustainable economy based on local potential.